Estimating the causal effect of alcohol consumption on well-being for a cross-section of 9 former Soviet Union countries. - Mentzakis, Emmanouil; Suhrcke, Marc; Roberts, Bayard; Murphy, Adrianna; McKee, Martin (Social Science & Medicine, 2013)
Abstract: While the adverse health and economic consequences attributable to alcohol consumption are widely acknowledged, its impact on psychological wellbeing is less well understood. This is to a large extent due to the challenge of establishing causal effects of alcohol consumption when using standard single-equation econometric analyses. Using a unique dataset collected in 2010/11 of 18,000 individuals and also community characteristics from nine countries of the former Soviet Union, a region with a major burden of alcohol related ill health, we address this problem by employing an instrumental variable approach to identify any causal effects of alcohol consumption on mental well-being. The availability of 24-h alcohol sales outlets in the neighbourhood of the individuals is used as an instrument, based on theoretical reasoning and statistical testing of its validity. We find that increased alcohol consumption decreases well-being and that ignoring endogeneity leads to underestimation of this effect. This finding adds a further and previously under-appreciated dimension to the expected benefits that could be achieved with more effective alcohol policy in this region.